When migraine mimics stroke: A systematic review. (December 2018) - Terrin, Alberto; Toldo, Giulia; Ermani, Mario; Mainardi, Federico; Maggioni, Ferdinando
Background: Migraine with aura may mimic an acute ischemic stroke, so that an improper administration of thrombolytic treatment can expose migrainous patients to severe adverse effects. Methods: This systematic review quantifies the relevance of migraine with aura among stroke mimics, checking for thrombolysis' safety in these patients. We reviewed the literature after 1995, distinguishing from studies dealing with stroke mimics treated with systemic thrombolysis and those who were not treated with systemic thrombolysis. Results: Migraine with aura is responsible for 1.79% (CI 95% 0.82–3.79%) of all the emergency Stroke Unit evaluations and it represents 12.24% (CI 95% 6.34–22.31%) of stroke mimics in the group not treated with systemic thrombolysis. 6.65% (CI 95% 4.32–9.78%) of systemic thrombolysis administrations are performed in patients without an acute ischemic stroke. Migraine with aura is responsible for 17.91% of these (CI 95% 13.29–23.71%). The reported rate of adverse events seems extremely low (0.01%). Conclusion: Migraine with aura is the third most common stroke mimic, following seizures and psychiatric disorders; it is responsible for about 18% of all improper thrombolytic treatments. Despite the absence of strong supporting data, thrombolysis in migraine with aura seems to be a procedure with an extremely low risk of adverse events.